Effect of treatment on disease incidence and productivity of sheep and goats in two groups of villages in the humid forest zone of southwest Nigeria - Adeoye, S.A.O. (1987)
A survey was carried out to evaluate the effect of veterinary treatment on disease incidence and productivity of West African Dwarf (Djallonke) goats and sheep from may 1982 to April 1983. Two village groups were identified as treatment group (where rinderpest vaccination and dipping applied) and control group (where no veterinary intervention took place). A total of 646 goats and 269 sheep (376 goats and 145 sheep in the treatment group and 270 goats and 124 sheep in the control group) entered the survey. Mortality rates of 28.1% and 4.5% were recorded among all goats in the control and treatment groups respectively; for sheep mortality rates of 8.9% and 2.8% were recorded among the control and treatment groups respectively. A doe on average produced 8.6 and 6.7 kg kid per year while an ewe produced 13.5 and 11.5 kg lamb per year in the treatment and control groups respectively for both species. Litter sizes were 1.53 and 1.49 for does and 1.28 and 1.23 for ewes among treatment and control groups respectively for both species. Kidding interval was 252 days for goats and 264 day for sheep among treatment groups, while 287 for goats and 282 for sheep among control group. Mean birth weight of kids was 1.6 kg among both treatment and control groups. From lambs mean birth weights recorded were 2.3 and 1.9 kg among treatment and control groups respectively. The mean weight of kids at 90 days were 4.7 kg and 5.3 kg and that of lambs were 9.1 kg and 8.6kg among treatment and control groups respectivelly. Daily weight gain was 34.4 g for goats and 75.5 g for sheep among treatment group and 41.1g for goats and 74.4g for sheep among the control groups.